Chapter Le narrazioni, nuove interazioni dei moderni. Lettura, cultura e pratiche digitali come presidi di identità - Morcellini, Mario (Moderna/Comparata, 2022)
The subject-text and author-reader relationship are investigated with particular attention to the current proliferation of narrative languages and methodologies, including digital ones. It reflects on the pedagogical and social value of an education that educates young people's active and conscious participation in the dynamics of contemporary society. The chapter adopts as a case study the modes of communication, including narrative, developed during the last two years deeply marked by the Covid19 pandemic. The function of processing insecurity, individual and collective, and reshaping behaviors of the different narrative forms are highlighted.